Man's nature and his potentialities towards a good moral quality - Abd Rashid, Adnan (The Institute of Islamic Understanding Malaysia, 2005)
Islam teaches man to believe in Allah and to follow His guidance and Laws in order to achieve peace of mind and heart then have a character that aims for perfection.In this way man be able to maintain and harmonise his personality with other people and the living system in society. Also man by his fitrah has a great potential to be come good. Allah has implanted into him the fitrah ready to accept truth and perform goodness. However this feature and quality of man is subject to change because of his freewill, the influence of environment and his inner nature.This article attempt to discuss on how his readiness to be good and ability to be bad, man physically and spiritually can be educated and developed through divine guidance in order to promote a good moral quality.